Does the Movement Competency Screen Correlate with Deep Abdominals Activation and Hip Strength for Professional and Pre-professional Dancers? - Justine Benoît-Piau; Mélanie Morin; Sylvie Fortin; Christine Guptill; Nathaly Gaudreault (International Journal of Sports Physical Therapy)
# Background Dancers are a unique category of athletes who are frequently injured and experience pain. The primary cause of dance injuries is overuse, which could potentially be prevented. However, literature is scarce regarding validated methods of evaluating the risk of injury in dancers. The Movement Competency Screen (MCS) could potentially fill this gap.